ImmunoPET: IMaging of cancer imMUNOtherapy targets with positron Emission Tomography: a phase 0/1 study characterising PD-L1 with 89Zr-durvalumab (MEDI4736) PET/CT in stage III NSCLC patients receiving chemoradiation study protocol. Issue 11 (18th November 2022) - Hegi-Johnson, Fiona; Rudd, Stacey E; Wichmann, Christian; Akhurst, Tim; Roselt, Peter; Trinh, Jenny; John, Thomas; Devereux, Lisa; Donnelly, Paul S; Hicks, Rod; Scott, Andrew M; Steinfort, Daniel; et al.
Abstract : Background: ImmunoPET is a multicentre, single arm, phase 0–1 study that aims to establish if 89 Zr-durvalumab PET/CT can be used to interrogate the expression of PD-L1 in larger, multicentre clinical trials. Methods: The phase 0 study recruited 5 PD-L1+ patients with metastatic non-small cell lung cancer (NSCLC). Patients received 60MBq/70 kg 89 Zr-durva up to a maximum of 74 MBq, with scan acquisition at days 0, 1, 3 or 5±1 day. Data on (1) Percentage of injected 89 Zr-durva dose found in organs of interest (2) Absorbed organ doses (µSv/MBq of administered 89 Zr-durva) and (3) whole-body dose expressed as mSv/100MBq of administered dose was collected to characterise biodistribution. The phase 1 study will recruit 20 patients undergoing concurrent chemoradiotherapy for stage III NSCLC. Patients will have 89 Zr-durva and FDG-PET/CT before, during and after chemoradiation. In order to establish the feasibility of 89 Zr-durva PET/CT for larger multicentre trials, we will collect both imaging and toxicity data. Feasibility will be deemed to have been met if more than 80% of patients are able complete all trial requirements with no significant toxicity. Ethics and dissemination: This phase 0 study has ethics approval (HREC/65450/PMCC 20/100) and is registered on the Australian Clinical Trials Network (ACTRN12621000171819). The protocol, technical and clinical data will be disseminated by conference presentations and publications. Any modifications to the protocol will be formally documented by administrative letters and must be submitted to the approving HREC for review and approval. Trial registration number: Australian Clinical Trials Network ACTRN12621000171819.